Long term continuous positive airway pressure (CPAP) and noninvasive ventilation (NIV) in children: Initiation criteria in real life. Issue 9 (25th April 2016) - Amaddeo, A.; Moreau, J.; Frapin, A.; Khirani, S.; Felix, O.; Fernandez‐Bolanos, M.; Ramirez, A.; Fauroux, B.
Summary: Introduction: Long term noninvasive continuous positive airway pressure (CPAP) and noninvasive ventilation (NIV) are increasingly used in children but limited information is available on the criteria and conditions leading to the initiation of these treatments. The aim of the study is to describe the objective overnight respiratory parameters and clinical situations that led to the initiation of CPAP/NIV in a pediatric NIV unit. Material and Methods: Retrospective analysis of the data of all the children discharged on home CPAP/NIV over a 1 year period. Results: Seventy‐six patients were started on CPAP (n = 64) or NIV (n = 12). CPAP/NIV was initiated because of CPAP/NIV weaning failure ( Acute group ) in 15 patients. None of these patients had an overnight gas exchange or sleep study before CPAP/NIV initiation. In 18 patients, CPAP/NIV was initiated on abnormal nocturnal gas exchange alone ( Subacute group ). These patients had a median of three of the following five overnight gas exchange abnormalities: minimal pulse oximetry (SpO2 ) <90%, maximal transcutaneous carbon dioxide (PtcCO2 ) >50 mmHg, time spent with SpO2 <90% or PtcCO2 >50 mmHg ≥2% of recording time, oxygen desaturation index >1.4/hr. In the last 43 patients, CPAP/NIV was initiated after an abnormal sleep study ( Chronic group ) on a mean of four of the aforementioned criteria and an apnea‐hypopnea index >10/hr. Conclusion: In clinical practice, CPAP/NIV was initiated in an acute, subacute and chronic setting with most patients having an association of several abnormal gas exchange or sleep study parameters. Future studies should evaluate the effectiveness and benefits of CPAP/NIV according to the clinical situation and initiation criteria.Pediatr Pulmonol. 2016; 51:968–974 . © 2016 Wiley Periodicals, Inc.